Genital invasion or perigenital spread may pose a risk of marginal misses for Intensity Modulated Radiotherapy (IMRT) in anal cancer. Issue 1 (December 2016) - Koeck, Julia; Lohr, Frank; Buergy, Daniel; Büsing, Karen; Trunk, Marcus; Wenz, Frederik; Mai, Sabine
Abstract Background While intensity modulated radiotherapy (IMRT) in anal cancer is feasible and improves high-dose conformality, the current RTOG/AGITG contouring atlas and planning guidelines lack specific instructions on how to proceed with external genitalia. Meanwhile, the RTOG-Protocol 0529 explicitly recommends genital sparing on the basis of specific genital dose constraints. Recent pattern-of-relapse studies based on conventional techniques suggest that marginal miss might be a potential consequence of genital sparing. Our goal is to outline the potential scope and increase the awareness for this clinical issue. Methods We present and discuss four patients with perigenital spread in anal cancer in both early and advanced stages (three at time of first diagnosis and one in form of relapse). Genital/perigenital spread was observed once as direct genital infiltration and thrice in form of perigenital lymphatic spread. Results We review the available data regarding the potential consequences of genital sparing in anal cancer. Pattern-of-relapse studies in anal cancer after conventional radiotherapy and the current use of IMRT in anal cancer are equivocal but suggest that genital sparing may occasionally result in marginal miss. An obvious hypothesis suggested by our report is that perigenital lymphovascular invasion might be associated with manifest inguinal N+ disease. Conclusions Local failure has low salvage rates in recent anal cancer treatment series. Perigenital spread may pose a risk of marginal misses in IMRT in anal cancer. To prevent marginal misses, meticulous pattern-of-relapse analyses of controlled IMRT-series are warranted. Until their publication, genital sparing should be applied with caution, PET/CT should be used when possible and meeting genital dose constraints should not be prioritized over CTV coverage, especially (but not only) in stage T3/4 and N+ disease.